Insights into the mechanism of vascular endothelial cells on bone biology. Issue 1 (29th January 2021) - Yin, Ying; Tang, Qingming; Xie, Mengru; Hu, Li; Chen, Lili
Abstract: In the skeletal system, blood vessels not only function as a conduit system for transporting gases, nutrients, metabolic waste, or cells but also provide multifunctional signal molecules regulating bone development, regeneration, and remodeling. Endothelial cells (ECs) in bone tissues, unlike in other organ tissues, are in direct contact with the pericytes of blood vessels, resulting in a closer connection with peripheral connective tissues. Close-contact ECs contribute to osteogenesis and osteoclastogenesis by secreting various cytokines in the paracrine or juxtacrine pathways. An increasing number of studies have revealed that extracellular vesicles (EVs) derived from ECs can directly regulate maturation process of osteoblasts and osteoclasts. The different pathways focus on targets at different distances, forming the basis of the intimate spatial and temporal link between bone tissue and blood vessels. Here, we provide a systematic review to elaborate on the function of ECs in bone biology and its underlying mechanisms based on three aspects: paracrine, EVs, and juxtacrine. This review proposes the possibility of a therapeutic strategy targeting blood vessels, as an adjuvant treatment for bone disorders.